Case Report: Novel compound heterozygous TPRKB variants cause Galloway-Mowat syndrome - Hiraide, Takuya; Hayashi, Taiju; Ito, Yusuke; Urushibata, Rei; Uchida, Hiroshi; Kitagata, Ryoichi; Ishigaki, Hidetoshi; Ogata, Tsutomu; Saitsu, Hirotomo; Fukuda, Tokiko (Frontiers in Pediatrics, 2024)
Background: Galloway-Mowat syndrome (GAMOS) is a rare genetic disease characterized by early-onset nephrotic syndrome and microcephaly with central nervous system abnormalities. Pathogenic variants in genes encoding kinase, endopeptidase, and other proteins of small size (KEOPS) complex subunits cause GAMOS. The subunit TPRKB (TP53RK binding protein) has been reported in only two patients with GAMOS with homozygous missense variants. Clinical report: Herein, we described a three-year-old male with GAMOS. He exhibited developmental delay, developmental regression, microcephaly, distinctive facial features, skeletal abnormalities, and epilepsy. Brain magnetic resonance imaging revealed progressive brain atrophy, delayed myelination, T2-hypointense signals in the thalamus, and multiple intracranial abnormal signals on diffusion-weighted imaging. He presented with relapsing nephrotic proteinuria exacerbated by upper respiratory tract infections and progressive renal function decline. Exome sequencing identified compound heterozygous missense and frameshift variants in TPRKB: c.224dup, p.(Ser76IlefsTer3) and c.247C>T, p.(Leu83Phe).Conclusions: Our study supportsthat pathogenic TPRKB variants cause KEOPS complex-related GAMOS.